Continuous Nanobelts of Nickel Oxide-Cobalt Oxide Hybrid With Improved Capacitive Charge Storage Properties - Harilal, Midhun; Syam, G. Krishnan; Lathakumary Vijayan, Binci; M., Venkatashamy Reddy; Adams, Stefan; Barron, Andrew R.; M. M., Yusoff; Rajan, Jose (Elsevier Ltd, 2017)
This paper reports the synthesis of continuous nanobelts, whose thickness is less than half of its pore diameter, of a material hybrid composing of nanograins of nickel oxide and cobalt oxide by electrospinning technique and their capacitive charge storage properties. While the constituent binary metal oxides (NiO and Co3O4) formed solid cylindrical nanofibers the hybrid and a stoichiometric compound in the Ni-Co-O system, i.e., spinel-type NiCo2O4, formed as thin nanobelts due to the magnetic interaction between nickel and cobalt ions. The nanobelts showed six-fold larger surface area, wider pores, and impressive charge storage capabilities compared to the cylindrical fibres. The hybrid nanobelts showed high specific capacitance (CS ~ 1250 F g− 1 at 10 A g− 1 in 6 M KOH) with high capacity retention, which is appreciably larger than found for the stoichiometric compound (~ 970 F g− 1 at 10 A g− 1). It is shown that the hybrid nanobelts have lower internal resistance (1.3 Ω), higher diffusion coefficient (4.6 × 10− 13 cm2 s− 1) and smaller relaxation time (0.03 s) than the benchmark materials studied here.